Blood product recalls in the United States. Issue 9 (27th May 2014) - McCullough, Jeffrey; Riley, Erinn; Lindgren, Bruce; Pulkrabek, Shelly; Hall, Ralph; Riley, William
<x xml:space="preserve">Abstract</x> Background The blood recall process is intended to remove from use products that may be harmful, but characteristics of recalls nationally have not been reported. Study Design and Methods We analyzed recalls of all blood products for 2010 and categorized the reason for the recall, the organizations producing the recalled products, and the Food and Drug Administration (FDA) district in which the blood was collected. Results During 2010, there were 2468 recalls involving 8278 blood products. None of the recalls was considered to have a reasonable probability of causing serious adverse health consequences or death (FDA Class I). The most common reasons for recalls were donation and donor qualification (73%) and finished product quality control (14%). The FDA class of recalls varied by recall reason, month of the year, FDA district, number of units of blood collected per FDA district, and number of units of blood collected by the blood center. The number of recalls per 100, 000 units of blood and the reason for recall varied by FDA district and blood centers collecting smaller numbers of units had more recalls. Conclusion The absence of Class I recalls suggests a high level of quality and safety in the US blood supply. Organizations that collected larger numbers of units of blood had fewer recalls and there may be some FDA influences since the number and reason for the recalls varied by FDA district.